Second World, Second Sex : socialist women's activism and global solidarity during the Cold War - Ghodsee, Kristen Rogheh, 1970- 1970- (Duke University Press, 2018)
Women from the state socialist countries in Eastern Europe-what used to be called the Second World-once dominated women's activism at the United Nations, but their contributions have been largely forgotten or deemed insignificant in comparison with those of Western feminists. In Second World, Second Sex Kristen Ghodsee rescues some of this lost history by tracing the activism of Eastern European and African women during the 1975 United Nations International Year of Women and the subsequent Decade for Women (1976-1985). Focusing on case studies of state socialist Bulgaria and nonaligned but socialist-leaning Zambia, Ghodsee examines the feminist networks that developed between the Second and Third Worlds and shows how alliances between socialist women challenged American women's leadership of the global women's movement. Drawing on interviews and archival research across three continents, Ghodsee argues that international ideological competition between capitalism and socialism profoundly shaped the world women inhabit today